The Pacific's connectivity and its trade implications - Matthias Helble (Asian Development Bank Institute (ADBI), 2014)
Pacific economies are confronted with several structural constraints that limit their economic growth, most importantly their small size and remoteness from major world markets. In this paper we study the importance of transport connectivity for Pacific economies when participating in the world economy. The paper first describes the evolution of trade flows of the Pacific economies over the last decade, in terms of both trade in goods and services. It then introduces two new datasets. One contains all shipping connections within the Pacific and with the rest of the world; the second all flight connections within the Pacific and with the rest of the world. Combining both datasets with the corresponding trade flows allows us to assess the importance of connectivity for the Pacific's trade performance. Using a gravity model approach, we find that a direct shipping connection more than doubles trade in goods. Similarly, countries with direct flight connections to the sending country welcome twice as many tourists. The frequency of transport connections is similarly important. Using an instrumental variables approach we are able to confirm the robustness of our results.
Keywords: F14; F15; R40; 330; trade integration; connectivity; transportation; trade costs